问题 解答题

已知ab≠0,求证:a+b=1的充要条件是a3+b3+ab-a2-b2=0.

答案

证明略

证明(必要性)

∵a+b=1,∴a+b-1=0,                                                2分

∴a3+b3+ab-a2-b2=(a+b)(a2-ab+b2)-(a2-ab+b2)                       5分

=(a+b-1)(a2-ab+b2)="0.                                          " 7分

(充分性)

∵a3+b3+ab-a2-b2=0,

即(a+b-1)(a2-ab+b2)=0,                                           9分

又ab≠0,∴a≠0且b≠0,

∴a2-ab+b2=(a-b2>0,

∴a+b-1=0,即a+b="1,           "                                      12分

综上可知,当ab≠0时,a+b=1的充要条件是

a3+b3+ab-a2-b2="0.                                            " 14分

选择题
选择题